Real-time navigation in 3D environments based on 2D sensor - Too, Zhi Loc (2019)
This report describes the use of a 2D LiDAR to navigate and map its surrounding environments. The 2D LiDAR is transformed into a 3D LiDAR with a motor to produce 3D map data. It is then used to do Simultaneous Localization and Mapping (SLAM). This report is segmented into hardware, which describes the hardware involved; programming, which describes the codes; discussions, which discusses the problems encountered and thought process. The device created was able to create a 3D static mapping of the environment and basic one directional mapping. Overall, this project is partly successful as it still cannot do a proper SLAM.